PENGARUH KESADARAN MEREK, CITRA MEREK DAN KOMUNIKASI PEMASARAN TERHADAP EKUITAS MEREK - Nurdiyanto, Ahmad Dwi; Purnomo, Mochamad (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2020)
AbstractThe brand in a product has a very important role as an identity and differentiator from other products. A brand is said to have equity if it can be recognized and remembered and embedded in the minds of consumers in one product class over other product brands. This study aims to determine the factors that influence brand equity of Herborist products at PT. Victoria Care Indonesia (VCI). This type of research used in this research is explanatory research with a quantitative approach. Samples were taken of 100 respondents from the consumer population of Herborist products. The results showed that both partially and simultaneously brand awareness was obtained, brand image and marketing communications had a significant effect on brand equity. With an influence contribution of 67%.Keywords : brand awareness, brand image, marketing communications, brand equity